(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Poor seed germination is the main obstacle for seed propagation of Rauwolfia tetraphylla L. in nature. The high viability (83.1%) of seeds in nature and the presence of viable embryo indicate that viability is not the only reason behind poor seed germination of this valuable medicinal plant. However, to overcome the problem of poor seed propagation, an efficient protocol has been developed for R. tetraphylla. Among the various treatments the maximum rate of ex vitro seed germination (13.33%) was found when the seeds were treated with 100 ppm of GA3. Response of in vitro germination was found to vary under different conditions. Not only that the rate was much higher compared to ex vitro germination. The rate of seed germination was found to be 78% in MS without PGR (plant growth regulator) supplements, while it was 70 and 78% in cotton bed under light and dark, respectively. It was 80% in incubator at 37ºC. In R. tetraphylla the hard seed coat is regarded as one of the barriers for germination and it can be easily eliminated by removing the hard seed coat. In vitro raised plantlets were reared in nature following proper acclimatization where they produced flowers as well as seeds. Apart from the said investigation, a method for in vitro shoot formation was also developed. Best response (90.7%) towards in vitro shoot regeneration was obtained from nodal segment when they were cultured on MS supplemented with 2.2 mg/l BA and 0.1 mg/l NAA. It took about 10-12 days to initiate shoots. About 9.9 ± 0.87 shoots were obtained per explants and their length was recorded as 2.28 ± 0.21 cm after six weeks. Various concentrations of IBA and NAA were used for in vitro root induction, but the in vitro raised shoots did not produce roots. Plant Tissue Cult. & Biotech. 30(1): 33-45, 2020 (June)